Increased vulnerability of family farming in the context of a weakened FNS agenda due to austerity measures in Brazil - Carlos Germano Ferreira Costa (Economía Agraria y Recursos Naturales)
SDG goals of ending poverty and achieving Zero Hunger must address the nexus of a transformational shift in the Food and Nutrition Security (FNS) Agenda, integrating more sustainable food systems, territorial development, sustainable infrastructure, fiscal and economic elements to robust social protection schemes. By considering Family Farming government expenditure budget, the slowing and stalled economic growth, and political and fiscal policy developments. We discuss Brazil's high-level government budgetary interventions, the governance and institutional contexts affecting food security as indicators of how aggressive budgetary and institutional measures have negatively impacted the nation's social protection policy environment, resilience, and sustainable development perspectives.